(untitled) (Revista de Psicología, 2024)
COVID-19 isolation has had diverse effects on child and adolescent populations. This study specifically analyzed the psychological dimension by considering the manifestations and coping strategies presented by children and adolescents from Buenos Aires aged 3 to 17 years. A total of 4,008 caregivers were surveyed online using a representative cluster sample from 83 schools. The most relevant results revealed that the prevalent psychological response was boredom, followed by restlessness/uneasiness. Furthermore, task-focused and avoidant coping strategies were associated with a smaller number of psychological manifestations, unlike those focused on emotion. The interest arises in investigating whether these psychological manifestations were configured during their evolution as persistent illnesses of greater scope.